Evil. Season two [videorecording (DVD)]. - King, Robert (Screenwriter); Herbers, Katja; Colter, Mike, 1976-; Emerson, Michael, 1954-; Mandvi, Aasif, 1966- (CBS, 2022)
In Season Two of Evil, Kristin struggles with her darker nature after killing a man, while David suffers temptation as he gets closer to his ordination. Meanwhile, Ben is visited by night terrors that prey on his greatest fears. Includes all thirteen episodes plus over 20 minutes of deleted scenes!